Metachronous Pancreatic Ductal Adenocarcinoma with Adjacent Serous Cystadenoma that Was Preoperatively Diagnosed by EUS-FNA: A Case Report and Review of the Literature - Yoshida, Michihiro (Intern Med, 2019)
Pancreatic serous cystic neoplasms (SCNs), such as serous cystadenoma (SCA), are generally recognized as benign because malignant counterparts of SCNs have been extremely rare. In clinical practice, pancreatic cystic neoplasms diagnosed as SCNs have been managed by conservative observation, as long as the patients remained asymptomatic. We herein report a case of metachronous ductal adenocarcinoma that was discovered during long-term follow-up of SCN and review the related literature. To our knowledge, this was the first reported case of the local presence of ductal adenocarcinoma adjacent to SCA that was preoperatively diagnosed by endoscopic ultrasound-guided fine-needle aspiration.